DISCUSSION OF SCIENCE ETHICS IN ISLAM: Reflections on Harun Nasution's Controversial Ethical Thought - Fattah, Abdul (ABHATS: Jurnal Islam Ulil Albab, 2020)
This article intends to examine the concept of scientific ethics in Islam with a focus on the thoughts of Harun Nasution.Harun Nasution is a controversial Islamic reformer. His idea was born as a response to and against the traditional ideas that developed at that time, even Harun Nasution dared to go against the flow of traditional thought ethics that had long been rusty and difficult to remove. The emphasis of this paper is on the presentation of Harun Nasution's progressive thinking in various main issues in the study of Islamic ethical thought, such as the idea of progress, coexistence between the Absolute- Textual (qath'i) and relative-contextual (zhanni) regions as a foundation the development of science in Islam, rational and traditional categorization, inclusive attitudes: accepting culture or knowledge from outside, freedom and development mentality: freedom of thought and action, cosmology: belief in causality as a source of success, moral problems and Harun Nasution's criticism of materialistic / hedonistic culture. This paper is presented considering that in a dynamic society, scientific ethics and community education play a role in determining the existence and development of society. Likewise with the role of scientific and educational ethics which is one form of manifestation of the ideals of Islamic life to preserve, transfer and instill (internalization) and transform Islamic values to the personal of the next generation, so that cultural-religious values are aspirated in society over time.